Peran Kebijakan Fiskal Islam Dalam Mengentas Kemiskinan Melalui Program Keluarga Harapan - Aminah Nur Habibah; Ruslan Abdul Ghafur; Erike Anggraeni; Anas Malik (Jurnal Ilmiah Ekonomi Islam, 2020)
This research was conducted to find the impact caused by one of the fiscal policy in alleviating poverty. This research was conducted with a qualitative approach to the method of collecting observation, documentation and interview data to the recipient community of the Hope Family Program assistance. The analysis used in this research is descriptive qualitative. The results of the study found that the implementation of the family of hope program in Ketapang District was running in accordance with the goals and objectives of the ministry of social policy in PKH. When viewed from the standpoint of Islamic economics the family hope program in Ketapang District is a positive activity in the welfare of people's lives by meeting the needs of which include Ad-daruriyyah needs, Al-hajjiyyah needs, and At-tahsiniyyah needs and Al-Kamiliyyah needs by not violating Islamic rules and law.